INTEGRATING LOCAL WISDOM INTO STEM EDUCATION TO ENHANCE SCIENTIFIC LITERACY IN REMOTE AND UNDERSERVED REGIONS - Brianna Le Busque; Anna Julita Foa; Ni Wayan Suparmi (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Science education in underdeveloped, frontier, and outermost regions faces major challenges, including low levels of scientific literacy among students, limited educational resources, and restricted access to quality education. To address these issues, this study aimed to develop and evaluate the effectiveness of a STEM learning model grounded in local wisdom (ethno-STEM) for enhancing students’ scientific literacy. This research employed a Research and Development (R&D) approach using the 4-D development model (Define, Design, Develop, Disseminate). The trial was conducted with 56 eighth-grade students from two junior high schools located in 3T areas in Ngada Regency, Indonesia. A quasi-experimental design was used, involving both experimental and control groups. Instruments included a scientific literacy test, student engagement observation sheets, and a student response questionnaire. The results indicated a significant improvement in scientific literacy within the experimental group. The average pre-test score increased from 54.6 to 82.3 in the post-test, with an N-Gain of 0.72 (classified as high) and a statistically significant t-test result (p < 0.05). In contrast, the control group showed an increase from 55.1 to 67.8 (N-Gain = 0.41, classified as moderate). Additionally, student engagement and enthusiasm improved, with 86% of students stating that the learning process was more engaging because it connected science content with local culture. In conclusion, the ethno-STEM model was found to be effective in improving students’ scientific literacy and is highly relevant for implementation. It is recommended that this model be more widely adopted as a culturally contextualized instructional strategy.